Maternity Confined: Mothering and Mental Illness in the British Columbia Provincial Insane Asylum Before World War I - Stanley, Heather (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2025)
The decision to commit a loved one for carceral treatment and care in a mental asylum was never an uncomplicated one. However, late nineteenth- and early twentieth-century families who had a loved one suffering from a mental illness caused by maternity faced additional logistical and social issues because of the societal and geographical realities of living in British Columbia. Using records from the British Columbia Provincial Insane Asylum, this article explores how settler-colonial families navigated these struggles as well as how insane mothers complicated idealized motherhood and the settler-colonial project in British Columbia as a whole.